The politics of zoom: Problems with downscaling climate visualizations. Issue 1 (30th January 2019) - Schneider, Birgit; Walsh, Lynda
Abstract : Following the mandate in the Paris Agreement for signatories to provide "climate services" to their constituents, "downscaled" climate visualizations are proliferating. But the process of downscaling climate visualizations does not neutralize the political problems with their synoptic global sources—namely, their failure to empower communities to take action and their replication of neoliberal paradigms of globalization. In this study we examine these problems as they apply to interactive climate‐visualization platforms, which allow their users to localize global climate information to support local political action. By scrutinizing the political implications of the "zoom" tool from the perspective of media studies and rhetoric, we add to perspectives of cultural cartography on the issue of scaling from our fields. Namely, we break down the cinematic trope of "zooming" to reveal how it imports the political problems of synopticism to the level of individual communities. As a potential antidote to the politics of zoom, we recommend a downscaling strategy of connectivity, which associates rather than reduces situated views of climate to global ones. Abstract : "Downscaled" climate visualizations are proliferating after the call for climate services in Paris 2015. But the "zoom" tool that many digital tools rely on brings with it political problems that disempower viewers and replicate neoliberal paradigms of globalization. This paper explicates those problems and suggests an alternate paradigm.